Feasibility of a Peer-Led Asthma and Smoking Prevention Project in Australian Schools with High Indigenous Youth - McCallum, Gabrielle B.; Chang, Anne B.; Wilson, Cate A.; Petsky, Helen L.; Saunders, Jan; Pizzutto, Susan J.; Choo Su, Siew; Shah, Smita (Frontiers in Pediatrics, 2017)
Background The high global burden of asthma and tobacco smoking among Indigenous people may potentially be reduced by appropriate interventions that target prevention of tobacco smoke uptake and improved asthma management. The latter includes targeted treatment based on airway inflammation. We undertook a feasibility study in two Darwin schools with a high proportion of Indigenous youth to determine the feasibility of an innovative, peer-led, school-based education program called the Asthma and Smoking Prevention Project (ASPP). A subset of children with reported persistent respiratory symptoms were also clinically evaluated to determine the lower airway inflammatory profile and optimize asthma management. Methods The ASPP is founded on an evidence-based three-step program and targets improving asthma management and preventing the uptake of tobacco smoking. The program uses a student-centered approach in which senior students (peer leaders) deliver the ASPP to Grade 7 students using activities, videos, and games. Students completed questionnaires related to asthma and smoking at baseline and 3 months after program delivery. Students with respiratory symptoms at 3 months were invited for a comprehensive clinical evaluation and tests including sputum induction. Results The ASPP was well received. Of the 203 students involved, 56 (28%) were Indigenous and 70% completed baseline and follow-up questionnaires. Self-reported asthma was high (19%), 10% of students reported smoking and 63% reported exposure to tobacco at home. Of the 22 students who were clinically evaluated, 41% were Indigenous. Clinically important airway inflammation was high; 23% had Fractional Exhaled Nitric Oxide Levels ≥35 ppb, 88% had airway neutrophilia (>15%), and 29% had airway eosinophilia (>2.5%). Optimization of medication and management was required in 59% of students. Conclusion Our study has demonstrated the implementation of the ASPP was well received by the schools as well as by the students. The high prevalence of clinically important airway inflammation and suboptimal asthma management highlights the need for a community-based study on persistent respiratory symptoms in adolescents to reduce the burden of chronic lung disease particularly for Indigenous Australians.